Differences between oligotrophic communities resulting from old-field succession in relation to bedrock - Puerto, A.; Rico, M. (Plant Ecology, 1994)
Dehesa ecosystems on granite and on slate clearly differ in soil characteristics. Our aim was to find out whether floristic composition differed too. We selected an equal number of plots, on both granite and slate, in different successional stages of development and at various ages after field abandonment (the youngest 15-20 years). Plots with rock-outcrops, which had never been cultivated, were also included in the study. The results showed that floristic differences between granite and slate communities were not detectable in the younger successional stages. However, they showed up with time and on stabilized grasslands became significant. But on plots with rock-outcrops the differences were not observable. This was undoubtedly influenced by the peculiar features of these plots, characterised by poor arid soils and surface parent material. In fact they did not show significant differences in the analysed soil parameters either. Species diversity and biomass showed a similar pattern of differences to floristic composition. The highest species diversity was found on plots with lower biomass (the youngest ones). The lowest biomass in conjunction with quite low species diversity was found on plots with rock-outcrops, which again is consistent with their peculiar features.
Keywords: biomass; diversity; granite; mediterranean grasslands; slate